Compensating the End-Effector Position of Semi- Flexible Robot Using Smart Structure Technique - Al-Khafaji, Hussein M.; Jweeg, Muhsin J. (Basrah Journal for Engineering Sciences, 2014)
This study proposed the using of a smart structure principle with a methodology for reducing the difference (error) between the actual position (for a semi-flexible robot) and the theoretically calculated position (for a rigid robot) on- line. The methodology depends on the interfering between the maps of the two cases; the rigid case (ideal), and the deformed case (actual) for compensation of error. According to this methodology, a class (program) was built using the visual Basic.Net; this class is called the compensation class. In this work, a two degrees of freedom articulated type lightweight semi-flexible robot was used. This robot is confined to move in a vertical plane. The smart structure system was represented by; the sensors for measuring the error deformation variables were mounted on the two links of the robot, Data acquisition (DAQ) system and the actuators of the joints. The smart structure robot systems were designed and built in this work. Also, to control the smart structure robot’s systems, software was built using Visual Basic.Net. Compensation tests have been achieved on the complete system to check the performance and results of the compensation system. This system showed a good improvement in the performance of robot for compensation and reduction in the error between the ideal position (rigid robot) and the practical position (measured position). The average error after the compensation reduced to 12.32 times in the x-direction and 21.76 times in the y-direction.